2020
DOI: 10.30813/psibernetika.v13i1.2272
|View full text |Cite
|
Sign up to set email alerts
|

Pola Asuh Orangtua Dan Kecenderungan Adiksi Game Online Pada Remaja Akhir Di Jakarta

Abstract: <p>Perkembangan teknologi memberikan dampak positif dan negatif terhadap penggunanya. Salah satu dampak negatif yang ditimbulkan adalah munculnya perilaku bermain online game sampai kecenderungan kecanduan. Tujuan penelitian ini bertujuan untuk mengetahui hubungan pola asuh orangtua dengan kecenderungan adiksi online game remaja akhir di Jakarta. Jenis penelitian yang digunakan adalah adalah penelitian korelasional dengan metode kuantitatif dengan menggunakan teknik non <em>random sampling</em&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Overall, each dimension of democratic parenting on the value factor held by parents and socio-economic with online game addiction tendencies has a significant relationship and has a positive correlation value (Yosephine & Lesmana, 2020). (Budiarti, Sustrami, & Febriani, 2022) Based on the results of the study, it can be concluded that there is a significant relationship between democratic parenting and smartphone addiction in students and there are several influencing factors such as socioeconomic and beliefs held by parents.…”
Section: Parenting Patterns Of Cirebon Mechanics Vocational School St...mentioning
confidence: 98%
“…Overall, each dimension of democratic parenting on the value factor held by parents and socio-economic with online game addiction tendencies has a significant relationship and has a positive correlation value (Yosephine & Lesmana, 2020). (Budiarti, Sustrami, & Febriani, 2022) Based on the results of the study, it can be concluded that there is a significant relationship between democratic parenting and smartphone addiction in students and there are several influencing factors such as socioeconomic and beliefs held by parents.…”
Section: Parenting Patterns Of Cirebon Mechanics Vocational School St...mentioning
confidence: 98%
“…Therefore, it can be assumed that authoritative parenting can incite online game addiction in children. 22,23 In the authoritarian parenting style, the parents are highly demanding but not responsive. They also restrict their child's autonomy.…”
Section: Original Articlementioning
confidence: 99%